Keterlambatan Pengobatan pada Penderita Leptospirosis di Kota Semarang - Rizki Amalia; Widya Hary Cahyati (Dian Nuswantoro Semarang, 2017)
Leptospirosis is an infectious disease that is endemic in the population of workers related to land. Rate fatality leptospirosis reached 5%, meaning that 5 of each case could die. Mortality in patients with leptospirosis is caused by several factors, including delays in treatment. Semarang city was the region with the highest leptospirosis cases in Central Java (75 cases in 2014 with 13 deaths). Based on preliminary studies, 8 of 15 patients who died of leptospirosishas been delayed treatment. This type of research was descriptive analysis with cross sectional approach. The number of samples was 53 respondents selected by simple random sampling technique. The independent variables consist of the level of knowledge, attitudes of patients, health seeking behavior, perception of treatment, and motivation for treatment, with the dependent variable in the form of delays in the treatment of patients with leptospirosis. The results showed that the variables associated with treatment delay of leptospirosis is the level of knowledge (p = 0.017) and health seeking behavior (p = 0.0001). Suggested their eforts to increase public knowledge to enhance the implementation of promotional and educational programs through counseling, mass media or electronic media.Keywords: Delay, Treatment, Leptospirosis